Respuesta :

x - y = 2
4x - 3y = 11.

Using Elimination method, eliminating x, multiply equation (i) by 4. Because of the 4 in the second equation.

x - y = 2  ...  (x4)
4x - 3y = 11.

4x - 4y = 8 
4x - 3y = 11.

The first minus the second.

(4x - 4x) -4y- -3y = 8-11
-4y + 3y  = -3
-y = -3.     Divide both sides by -1
y =3.

Substitute this value into the very first equation

x - y = 2,  y = 3
x - 3 = 2
x = 2 + 3 = 5.

Therefore  x = 5,  y = 3.
-4[x-y=2[
4x-3y=11
-4x+4y=-8
0+y=3
y=3 now, i am going to find x value. put 3 on y value to get x value
i want use easy way because x-y=2 is easy to get x value.
x-3=2
x=2+3
x=5 right now, i am gonna check my answer if it's wrong
i am going to take x-y=2 because its easy to check my answer
x-y=2
x = 5, y=3 so i am gonna check it.
5-3=2 so the answer is x=5, y=3
 
ACCESS MORE